Tax Planning at PT Station Sumber Makmur Jaya Samarinda - Budiman, Arief; Iskandar (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
The purpose of this study is to analyze and find out how much savings can be made by PT. Sumber Makmur Jaya Samarinda Station in conducting tax planning (Tax Planning) through the method of depreciation of fixed assets and fiscal adjustment based on Law Number 36 of 2008 and Regulation of the Minister of Finance for the purpose of minimizing tax burden or saving income tax owed to the company. This study collects facts and identifies data that discusses tax planning problems through the determination of fixed asset depreciation methods and fiscal adjustments to the tax burden borne by the company. The results of this study are expected to provide input to the company's management in depreciating fixed assets and fiscal adjustments to income to optimize the tax burden that will be experienced as a result of using depreciation and fiscal adjustment methods. PT. Station Sumber Makmur Jaya needs to seriously consider the profits, profits and losses experienced as a result of using depreciation and fiscal adjustment methods. The conclusion of this study is that PT. Station Sumber Makmur Jaya in determining the method of depreciation of fixed assets is appropriate, but the company has not fully understood about fiscal adjustments for the purpose of minimizing the tax burden that will be payable